Enhanced continental weathering drove a transient oxygenation event during the largest Ediacaran carbon isotope excursion - He Sun; Yilin Xiao; Yangyang Wang; Fengtai Tong; Hai-Ou Gu; Can Ge; Fangyue Wang; Zhihui An; Erhao Shan; Meng Zhang; Tingyu Yang; Pengju Liu (Communications Earth & Environment)
Abstract The largest Ediacaran carbon isotope excursion (the Shuram excursion, SE) has been proposed to coincide with a transient oceanic oxygenation event. However, the mechanisms responsible for the SE and the associated oxygenation remain unclear. In this study, we investigated the role of silicate weathering during the SE by measuring Li isotope compositions from two suites of marine carbonates in the Ediacaran Doushantuo sections. Our results reveal a pronounced negative lithium isotope excursion during the SE, which cannot be attributed to mineralogical effects and argues against a diagenetic origin for the SE. Instead, box model simulations of lithium-strontium cycles suggest a pulsed phase of enhanced congruent continental weathering during the SE. This increased weathering would have significantly elevated the input of essential nutrients into the ocean, boosting primary production, which in turn led to transient oceanic oxygenation. This process may also explain the negative δ13Ccarb excursion, as it could result from the oxidation of upwelling dissolved organic carbon in shallow seawater. Continental weathering likely played a crucial role in regulating climate, seawater chemistry, and Earth’s surface oxidation state during the SE.